1980
DOI: 10.1128/jvi.33.2.830-844.1980
|View full text |Cite
|
Sign up to set email alerts
|

Head maturation pathway of bacteriophages T4 and T2. V. Maturable epsilon-particle accumulating an acridine-treated bacteriophage T4-infected cells

Abstract: A maturable head-related particle of bacteriophage T4 has been identified and characterized. This e-particle has the same size as the prehead, but its shell is made of the cleaved product of gene 23 (gp23*). It contains internal matter, most likely the processed core proteins, which is lost or modified by experimental manipulation. It accumulates, together with partially filled ("grizzled") heads, in T4-infected cells that are treated with 9-aminoacridine. On sections of "wellpreserved" cells the E-particles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Upon phage infection these proteins [the internal proteins (IPs), IPI, IPII, IPIII and Alt] are injected into the host together with the DNA (Black et al ., 1993). Addition of the phage T4 terminase inhibitor 9‐aminoacridine (9AA) to infected bacteria blocks DNA packaging and leads to the accumulation of fully processed mature T4 proheads that contain the cleaved IPs but lack DNA (Schaerli and Kellenberger, 1980).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon phage infection these proteins [the internal proteins (IPs), IPI, IPII, IPIII and Alt] are injected into the host together with the DNA (Black et al ., 1993). Addition of the phage T4 terminase inhibitor 9‐aminoacridine (9AA) to infected bacteria blocks DNA packaging and leads to the accumulation of fully processed mature T4 proheads that contain the cleaved IPs but lack DNA (Schaerli and Kellenberger, 1980).…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of φKZ with the T4 terminase inhibitor 9AA was generally as described for T4 (Schaerli and Kellenberger, 1980), with the exception that preliminary experiments were undertaken to determine the concentration of 9AA required to inhibit phage particle production (15 µg ml −1 ); the concentration that was subsequently used was 10‐fold higher than required for the same effect on T4. This can be attributed, in part, to the higher tolerance of P. aeruginosa to 9AA than E. coli (Wainwright et al ., 1997) .…”
Section: Methodsmentioning
confidence: 99%
“…This purified material migrated slower on SDS-PAGE gel since the enzyme–Hoc was 40 kDa larger than enzyme–SC ( Figure S3 ). Tailless ΔHoc T4 capsids were produced from ΔHoc T4 phage with a yield of 1–3 mg/L in the presence of 9-aminoacridine, which blocks genomic DNA packaged into the capsids and thus results in no tail attachment to the capsids (Schaerli and Kellenberger, 1980 ). They show faster electrophoretic mobility than WT T4 capsids as indicated in Figure 1C (lanes 4 vs. 6).…”
Section: Resultsmentioning
confidence: 99%
“…A second lesson is that ipDNA-containing capsids are detectable by EM of thin sections. In a study of phage T4, ipDNA-containing capsids are observed as the Bgrizzled^particles of Schaerli and Kellenberger (1980), for example. These particles appear to be intermediates of DNA packaging and are potential targets of future, more advanced studies.…”
Section: Related Past Data From Several Phagesmentioning
confidence: 99%